2006
DOI: 10.1124/jpet.105.099499
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Drug Doxorubicin Inhibits Liver Fibrosis in Bile Duct-Ligated Rats and Can Be Selectively Delivered to Hepatic Stellate Cells in Vivo

Abstract: Hepatic stellate cell (HSC) proliferation is a key event in liver fibrosis; therefore, pharmacological intervention with antiproliferative drugs may result in antifibrotic effects. In this article, the antiproliferative effect of three cytostatic drugs was tested in cultured rat HSC. Subsequently, the antifibrotic potential of the most potent drug was evaluated in vivo. As a strategy to overcome drug-related toxicity, we additionally studied how to deliver this drug specifically to HSC by conjugating it to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…HepG2 HCC cells activated HSCs through HBs in our study, in accordance with the above-mentioned findings. The inhibition of HSCs proliferation is considered to be the most important strategy for anti-fibrotic therapy (28). Our results indicated that inhibiting the HBs receptor expression may be a target for the treatment of the liver fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…HepG2 HCC cells activated HSCs through HBs in our study, in accordance with the above-mentioned findings. The inhibition of HSCs proliferation is considered to be the most important strategy for anti-fibrotic therapy (28). Our results indicated that inhibiting the HBs receptor expression may be a target for the treatment of the liver fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…The concentration of Dox was measured directly because it naturally fluoresces at 515 nm after excitation with 480 nm light48. Medium containing 10 μM Dox was delivered to the device at 3 μL/min for 32 hours at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore HCS activation is associated with stellate cell proliferation, increased contractility and enhanced extracellular matrix production [11,22,23]. Therefore, HSCs play a crucial role in cellular and molecular events that lead to hepatic fibrosis [6,22,23].…”
Section: Discussionmentioning
confidence: 99%